Primary chaetotaxy of the larval head capsule and head appendages of the Hydrophilidae (Coleoptera) based on larva of Hydrobius fuscipes (Linnaeus, 1758) - Fikáček, Martin; Archangelsky, Miguel; Torres, Patricia L. M. (Zootaxa, 2008)
The primary chaetotaxy of the larval head capsule and head appendages of the family Hydrophilidae (Insecta: Coleoptera) is described and illustrated using the larva of Hydrobius fuscipes (Linnaeus, 1758) as a model, and compared with fifteen hydrophilid taxa representing all main taxonomic groups within the family; brief comparative notes with representatives of the families Helophoridae, Spercheidae, Hydrochidae and Histeridae are also provided. Primary chaetotaxic nomenclature is developed for the Hydrophilidae, allowing the use of chaetotaxic characters for phylogenetic studies as well as diagnostic purposes. The study of representatives of the families Helophoridae, Hydrochidae and Spercheidae suggests that this nomenclature can also be effectively applied to other hydrophiloid families. Chaetotaxic nomenclature systems used in larvae of other groups of Coleoptera are briefly reviewed.